ANALISIS PERTANGGUNG JAWABAN PIDANA DOKTER ( Studi Putusan Mahkamah Agung No 365K/Pid/2012) - Heni Widiyani; Syafruddin Kalo; Marlina Marlina; Mahmud Mulyadi (USU LAW JOURNAL, 2016)
ABSTRACT Doctor is a profession devoted to the science of public interest, to have freedom of humanitarian values under the code of medical ethics. Relationship between doctor and patient that originated from the paternalistic relationship turns into a horizontal contract. The amendment raises a lot going on criticism of the performance of doctors. The formulation of the issues discussed in this study regarding the rules on malpractice in Indonesian positive law and criminal liability of doctors in the Supreme Court decision No. 365k/pid/2012. This problem is analyzed with the theory of criminal responsibility and theories of causality. Results of this thesis research on the rule of positive law malpractice in Indonesia is in the book of the Criminal Justice Act, Act No. 36 of 2009 on Health, and Law No. 29 of 2004 Practice of Medicine, malpractice is divided into two, judicial malpractice and malpractice etic. Criminal liability imposed on physicians by the Supreme Court is not in accordance with the theory of causality because there are no omissions in the action taken by the doctor that resulted in the death of the victim, so that the elements of Article 359 of the accused are not being met, and there should be no criminal responsibility for the death of the victim to the doctor, as a result of death due to embolism is a medical risk in medicine and included in the justification of criminal responsibility. So the Supreme Court's decision in giving the verdict of guilt was not right and wrong. well as law enforcement officers to more thoroughly and understand the principles of law and legal theory and laws and regulations related to shrimp malpractice, resulting in a wise decision for the court physicians and patients in conflict of the law.